EFEKTIVITAS TERAPI TUINA CHUZEN DAN FOOD TERAPI DALAM PROSES PENYEMBUHAN IBU HAMIL DENGAN ANEMIA - Wijono Sukaputra Agussalim; Frisca Desma Ayu Kusuma Wardani; Muhamad Fahmilza Bachri (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2022)
Background : As a result of the red blood cell-forming tissues' failure to produce enough red blood cells to keep hemoglobin levels at normal levels, anemia is a condition marked by lower-than-normal blood hemoglobin levels. Objective: Identify the efficacy of food treatment and therapytuina chuzen in the recovery of pregnant women with anemia Method : The technique that involves giving patients or clients direct instruction or demonstration Result : The use of moringa plants can improve blood circulation. Healthy blood circulation can improve fertility. Suggestion : When deciding how much to consume given a pregnant woman's health, it is advised that she contact an obstetrician. Keywords : tuina chuzhen, akupuntur, anemia, and diet Chinese herbal medicine